2022
DOI: 10.1111/soc4.12964
|View full text |Cite
|
Sign up to set email alerts
|

Gender and innovation through an intersectional lens: Re‐imagining academic entrepreneurship in the United States

Abstract: How to study inequality in innovation? Often, the focus has been gender gaps in patenting. Yet much is missing from our understanding of gendered inequality in innovation with this focus. This review discusses how gender and innovation are intertwined in durable academic inequalities and have implications for who is served by innovation. It summarizes research on gender and race gaps in academic entrepreneurship (including patenting), reasons for those longstanding inequities, and concludes with discussing why… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…These researches refer generically to the concept of innovation in the context of a business organization, without specifying its type, source, or mode of implementation Exposito et al, 2023;Gaies et al, 2023;Mickey and Smith-Doerr, 2022.…”
Section: Generic Innovationmentioning
confidence: 99%
“…These researches refer generically to the concept of innovation in the context of a business organization, without specifying its type, source, or mode of implementation Exposito et al, 2023;Gaies et al, 2023;Mickey and Smith-Doerr, 2022.…”
Section: Generic Innovationmentioning
confidence: 99%
“…For example, rather than assume that the implications of identifying with a minoritized racial/ethnic group in a particular context will be similar for both men and women, an intersectional approach starts from the assumption that individuals with each combination of gender and racial/ethnic identity will have unique experiences (Essers et al, 2010). While research in entrepreneurship has considered the influence of intersecting racial/ethnic, gender, social class, and religious identities (Dy and Agwunobi, 2019;Romero and Valdez, 2016;Vorobeva, 2022), only a few studies have focused on academic entrepreneurship, specifically (Jackson et al, 2022;Mickey and Smith-Doerr, 2022;Nelson, 2020). One focusing on women of color found that barriers to program effectiveness included institutional hurdles, negative interpersonal interactions during instruction, and challenges to entrepreneurial identity (Jackson et al, 2022).…”
Section: Need For An Intersectional Approachmentioning
confidence: 99%
“…The emphasis on research conducted by more than one individual in an interdependent fashion has led to the concept of team science and focused research on the group dynamics of scientific teams working towards a common objective (Hall et al 2018;National Research Council 2015). This, in turn, generated empirical research on the impact of gender on innovation activities related to software development (Ortu et al 2017), small businesses (Zastempowski & Cyfert 2021), and academic entrepreneurship (Mickey & Smith-Doerr 2022). Ethnicity, on the other hand, has received scant attention since it is difficult to assess with publicly available data.…”
Section: Introductionmentioning
confidence: 99%